(untitled) (REMUNOM, 2024)
Introduction: Multiple myeloma is a hematologic neoplasm characterized by the abnormal proliferation of plasma cells. Recently, anti-CD38 monoclonal antibodies have integrated into treatment regimens, demonstrating a promising depth of response. Objective: To evaluate the impact on progression-free survival and minimal residual disease of patients with Multiple Myeloma undergoing quadruple therapy. Method: This is a Systematic Prognosis Review, which posed the following guiding question - “Do patients with Multiple Myeloma who are treated with quadruple therapy have a positive impact on surviva and minimal residual disease?”. The DeCS (“Survival Rate” or “Survival Analysis” and “Drug Therapy” and “Multiple Myeloma” and “Antibodies, Monoclonal”) were then searched for in the databases according to the applicability of the inclusion criteria, which are cohort articles. Excluding duplicates and those that did not answer the question, resulting in nine articles. Results: Analysis of the findings revealed that 66.7% of the studies reported an increase in overall and progression-free survival, while 22.2% indicated no improvement in either survival. With regard to minimal residual disease, the majority of the studies analyzed yielded negative results (66.7%). On the other hand, 22.2% said there had been no change. Conclusion: It is inferred that quadruple therapy had an impact on increasing overall and progression-free survival and on the negativity of minimal residual disease, especially when performed with an anti-CD38 monoclonal antibody. However, studies comparing quadruple therapies are needed to ensure clinical applicability with a more robust level of evidence.